PENGEMBANGAN LKS BERORIENTASI KECAKAPAN HIDUP PADA MATERI SISTEM INDERA MANUSIA UNTUK SISWA SMA KELAS XI - ISTININGRUM, RENI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
The rule of education ministry and BSNP strengthen that the curriculum of formal and non-formal educations have the importance to develop learning which is oriented to life skill. The skill has its purpose to reach the students’ competence for their survival and adaptation in order to be successful in their life. Based on this explanation, the researcher developed a student worksheet which is oriented to life skill using 4-D model. The goal of the development of the student worksheet oriented to life skill which is practiced and can be prepared at school. The results showed that the worksheet valid from identity component, technical, construction, content and the life skill characteristics. The students’ positive response to the student worksheet which is oriented to life skill reach 84% with a good category. Keyword: Student Worksheet, Life skill, Human Sense